Les interactions médicamenteuses chez des patients sous chimiothérapie : Étude réalisée au service d’hématologie clinique de HMIMV-RABAT - berdi, Fadoua; Abderrahim, Baimyk; Jihane, Ifezouane; Yassine, Atbib; Hicham, Elmaaroufi; Kamal, Doghmi; Yassir, Bousliman (Jour Med Resh and Health Sci, 2023)
Drug interactions are a major source of therapeutic failure, non-compliance or potentially serious and life-threatening accidents. The risk of drug interactions and the associated adverse effects are higher in cancer patients because they frequently receive several drugs at the same time. In this context, we conducted a comparative prospective descriptive and analytical study, spread over a period of 8 weeks from January 6, 2020 to February 28, 2020, on drug interactions in the clinical hematology department of the HMIMV, RABAT whose objective was to determine the rate and distribution of drug interactions. The prevalence of drug interactions was 29.90%. The average age of our patients were 54±20.63 years with extremes ranging from 19 years to 84 years with a male predominance (69%). The mean number of drugs in our cross section was 7.52±3.19 and in those with drug interactions (10.50 ± 3.1). In our study, the rate of drug interactions was significantly higher in patients with 7 or more drugs (p<0.05), in those over 45 years of age (p<0.05). These results show that better coordination between pharmacist-physicians and the various health professionals seems essential to prevent dug interactions and improve patient management.